Future of media in Asia artificial intelligence, digital technology and media practice - Arao, Danilo Araña; Lim, Weng Marc; Cheong, Huey Fen ([Switzerland] Springer, 2025)
One of a series of titles on the Futures of Asia, “Future of Media in Asia” explores diverse facets of Asia's media landscape during the transformative 2020s, offering insights into pivotal transformations and potential trajectories. The covered topics include artificial intelligence, digital technology, and media practice. Examining the topics from corporate foresight and past-future to technological trends and environmental shifts, this book showcases a collaborative effort from multidisciplinary researchers navigating the complexities of forecasting and envisioning Asia's media futures. This book offers valuable insights to the dynamic discourse on future studies while offering a nuanced understanding of the possibilities that lie ahead of Asia as well as deciphering Asia's evolving impact and roles within the broader global context. An insightful read for scholars with an interest in Asian media and future studies.
Available to the general public.
Includes bibliographical references
Keywords: Mass media -- Asia; Artificial intelligence -- Social aspects; Communication -- Technological innovations